Synthesis and study of phospate-polyalkyleneoxide flotation reagent for oxidized minerals (International Journal of Biology and Chemistry, 2014)
Polyalkylene oxidephosphates were obtained by phosphorylation of polyethylene oxide and polypropyleneoxide of different molecular weight. Evaluation of flotation activity in experiments on the extraction of tungsten oxide from wolf ramite pulp showed that the introduction of oxygen donor atoms into phosphate group substituent, responsible for hydrophobization of the surface of mineral particles, increase the degree of the heavy metal extraction.